The Evolution of Working Capital Management Research - Mohd Ridzuan, Darun; Roudaki, Jamal; Radford, Jack (Medwell Journals, 2015)
This study aims to develop an llllderstanding about the evolutionary process of Working Capital Management (WCM) research, explaining WCM in particular environments from the l 900's rmtil the present. The study discusses relevant studies in the literature, exploring the relevance of models, concepts or frameworks developed to serve managers needs in particular operating environments and speculating future research directions. The evolution of WCM and influencing factors illustrate the integrative nature of WCM, appears to be dynamic as changes in managerial focus would reflect how companies manage WCJ\1 components. However, the review reveals that the WCM literature WIBble to provide relevant information to explain WCM in cwrent environment. The study is particularly value in making sense of WCM research today and likely future directions. The pathway of development while vital for research exposes needs and responds that is flllldamental for forecast of future prospects of WCM.